2006
DOI: 10.1007/s00064-006-1166-2
|View full text |Cite
|
Sign up to set email alerts
|

Die Behandlung der Apophysenabrissverletzung des Epicondylus ulnaris im Kindesalter

Abstract: From January 1, 1994 to December 31, 2003, 25 children with an average age of 12 years suffering from medial epicondylar avulsion fractures were operated on using open reduction and Kirschner wire fixation. An average of 3 years after the injury 14 of these children underwent follow-up examination using a procedure that took subjective, clinical and radiologic parameters into account. Two children showed a slight reduction in overall strength of the injured extremity when compared with the contralateral extrem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 10 publications
1
16
0
Order By: Relevance
“…To these authors, temporary apophysiodesis with screw in the preadolescent group is also relatively contraindicated; they recommend screw fixation only for adolescents [22,24]. We agree with this concept that K-wire fixation should be used in the very young.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…To these authors, temporary apophysiodesis with screw in the preadolescent group is also relatively contraindicated; they recommend screw fixation only for adolescents [22,24]. We agree with this concept that K-wire fixation should be used in the very young.…”
Section: Discussionsupporting
confidence: 53%
“…Reducing a fracture with K-wire fixation only stabilizes the injury without compressing fracture fragments. Although the screw may cause uncomfortable prominence and the need for subsequent hardware removal [24], we believe that this should not deter the orthopedist from performing an open reduction to achieve complete union of medial epicondylar fractures, and this view has been supported by other experts [25]. Furthermore, the risk of symptomatic non-union is clearly evident when using either non-operative management or simple K-wire fixation that does not employ compression principles [15].…”
Section: Discussionmentioning
confidence: 85%
“…Seven papers were excluded because they did not fulfill the pediatric population criteria [2, 98–103]. Five articles were primary radiographic articles with no focus on the treatment of medial epicondyle fractures [104108]. …”
Section: Methodsmentioning
confidence: 99%
“…[8][9][10]18 For more displaced fractures, numerous series have shown equally good outcomes among patients treated conservatively with a long arm cast and open reduction and internal fixation. 3,5,[8][9][10]15,17,18,20 Analogous to rupture of the ulnar collateral ligament in baseball pitchers, more extreme valgus instability associated with the pitching motion secondary to malunion or nonunion in youth baseball players may limit performance but not interfere with elbow function performed during activities of daily living. 16,27 Gilchrist et al 11 reported a case series of 5 patients who had suboptimal outcomes, with late valgus instability and inability to participate in throwing activities after nonoperative management of medial epicondyle fractures.…”
Section: Discussionmentioning
confidence: 95%
“…Much debate within the literature exists about optimal treatment of medial epicondylar fractures. 3,5,[8][9][10]15,17,18,20,26 Most authors agree that nondisplaced or minimally displaced fractures, defined as 0 to 5 mm of displacement, are best treated with a brief period of immobilization. [8][9][10]18 For more displaced fractures, numerous series have shown equally good outcomes among patients treated conservatively with a long arm cast and open reduction and internal fixation.…”
Section: Discussionmentioning
confidence: 99%